Estimation of wireless channel fading model in maritime communication for complex meteorological environment - Yasheng DAI; Bolin MA; Guangxue YUE (Dianxin kexue)
Due to the influence of complex marine environmental factors such as sparse scattering of electromagnetic wave on the ocean surface, wave shadow fading, complex meteorological environment.It is extremely hard to model the fading of wireless channel in maritime communication environment.After analyzing the influence of meteorological environment and multipath channel fading via direct-path, specular-path and diffuse-path on marine wireless communication channel fading, the estimation of wireless channel fading model in maritime communication for complex meteorological environment (EWCFM-CME) was proposed.An improved bee colony algorithm was designed to estimation the parameter of EWCFM-CME.In order to improve the efficiency and accuracy of search algorithm, an iterative function with sin(·) function as operator was designed in search scheme of bee colonies.The leading bee received the detection bee solution to update itself with probability P.It prevents the solution algorithm from falling into local optimization.The simulation results show that, compared with fluctuate two-ray (FTR) fading model and round earth loss (REL) model, the mean absolute error (MAE) of EWCFM-CME increased by 13.58% and 11.43% By comparing EWCFM-CME with cuckoo search, genetic algorithm and simulated annealing algorithm, the search time is reduced by 60.48%, 45.18% and 43.23%, respectively.